Multilayers of poly(ethyleneimine)/poly(acrylic acid) coatings on Ti6Al4V acting as lubricated polymer‐bearing interface. Issue 5 (6th January 2020) - Deng, Yaling; Sun, Jianjun; Ni, Xingya; Xiong, Dangsheng
Abstract: To achieve an efficient lubricated interface on titanium alloy (Ti6Al4V) alloy, polyelectrolyte multilayer (PEM) polymer coatings, based on poly(ethyleneimine)/poly(acrylic acid) (PEI/PAA), were fabricated on the surface of Ti6Al4V alloy substrates using the layer‐by‐layer (LbL) assembly technique. Their composition and morphology were confirmed by Fourier‐transform infrared/attenuated total reflectance (FTIR/ATR) spectroscopy, X‐ray photoelectron spectroscopy, and scanning electron microscopy. The tribological properties were investigated by a ball‐on‐disk rotating tribometer using deionized water, saline, and calf serum. The results exhibit that (PEI/PAA)* n coatings have the internal cross‐linked network and porous structure on the surface. The surface of PEI/PAA coatings‐modified Ti6Al4V shows the sufficient wettability. The polymer‐bearing interface of (PEI/PAA)*10 exhibits a low friction coefficient, 0.059, for 2 hr, and represents an 88% decline compared with bare Ti6Al4V. Moreover, the wear track on the polymer‐bearing interface is superlow. There is no obvious wear volume, which indicates effective wear resistance. The hydrated layer, the cross‐linked network structure, and the porous structure of PEM coatings are the main factors for efficient tribological properties. The multilayer PEI/PAA coating shows the potential uses of developing the lubricated‐bearing interface on Ti6Al4V alloy.